The importance of “Results of the direct production process” for the contemporary reading of Marx - Ratajczak, Mikołaj (Hybris, 2014)
The article presents the importance of Marx’s manuscripts know today as Results of the Direct Production Process for the contemporary reading of his critique of political economy. The “unpublished sixth chapter” of Capital enables us to reconstruct Marx’s attempts to resolve two problems that accompanied him during his work on political economy, one being the relation between the process of capital’s circulation and the process of capital’s production, and the other being the unity of the labor process and the valorization process. The importance of Results goes even further, allowing a reinterpretation of Capital that focuses on the becoming of capital, the moment of labor’s subsumtion, application of science to the production process and the establishment of the wage relation. What the first volume of Capital presents as an accomplished project, “the sixth chapter” presents as a process in becoming.